بعض أنواع القلق الرياضي وعلاقتها بدقة أداء مهارتي الإرسال وإستقبال الإرسال للاعبين الشباب بالكرة الطائرة - القيسي، ثائر داود سلمان; الماجد، أمجاد عبدالحميد بدر (دار الأطروحة للنشر العلمي, 2020)
أن ظاهرة القلق الرياضي أصبحت مهمة لدى العديد من علماء النفس الرياضي لما لها من دورا مهما في الإنجاز والنتيجة التي يمكن الحصول عليها، وعليه فهو سلاح ذو حدين فأما أن يكون تأثيره سلبيا فهو (قلق معوق) وأما أن يكون تأثيره إيجابيا فهو (قلق ميس)، وتكمن أهمية البحث بكونه محاولة للوقوف على تلك السمة والحد منها على قدر الإمكان إيمانا من الباحثان لتطوير المستوى المهاري اللاعبين الشباب بالكرة الطائرة. ويهدف البحث إلى: 1. التعرف على درجات أبعاد مقياس القلق الرياضي (القلق الميسر والقلق المعوق) لدى لاعبي الكرة الطائرة الشباب. 2. التعرف على نوع العلاقة ما بين أبعاد مقياس القلق الرياضي (القلق الميسر والقلق المعوق) مع مهارتي الإرسال واستقبال الإرسال لدى لاعبي الكرة الطائرة الشباب وقد تمثلت عينة البحث باللاعبين الشباب بالكرة الطائرة لأندية بغداد المشتركين في الموسم الرياضي 2018-2019 والبالغ عددهم (108) لاعبا. وقد تم استخدام مقياس القلق الرياضي وأبعاده (القلق الميسر والقلق المعوق)، واختباري (الإرسال، واستقبال الإرسال)، وبعد جمع البيانات ومعالجتها إحصائيا تم التوصل إلى مجموعة من الاستنتاجات هي: 1. وجود فرق ذات دلالة معنوية بين بعد (القلق الميسر) مع مهارتي الإرسال واستقبال الإرسال بالكرة الطائرة للشباب لأندية محافظة بغداد في حالتي ارتفاع أو انخفاض درجة البعد. 2. وجود فرق ذات دلالة معنوية بين بعد (القلق الميسر) مع مهارتي الإرسال واستقبال الإرسال بالكرة الطائرة للشباب لأندية محافظة بغداد. 3. وجود فرق ذات دلالة معنوية بين الدرجة الكلية (لمقياس القلق الرياضي) مع مهارتي الإرسال واستقبال الإرسال بالكرة الطائرة للشباب لأندية محافظة بغداد. أما التوصيات فهي: 1. ضرورة الاهتمام بما توصلت إليه الدراسة الحالية من أهمية معرفة درجة القلق الرياضي لكل لاعب ومقدار تأثرها على الأداء المهاري بالكرة الطائرة. 2. ضرورة إجراء دراسات مشابهة للتعرف على نوع العلاقة بين القلق الرياضي مع المهارات الهجومية والدفاعية بالكرة الطائرة والتي لم يتم تناولها بالدراسة الحالية. 3. ضرورة إجراء دراسات مشابهة يتم تناول متغيرات نفسية أخرى لم يتم تناولها بالدراسة الحالية ومحاولة معرفة نوع العلاقة مع المهارات الأساسية بالكرة الطائرة ولكلى الجنسين.
The phenomenon of mathematical anxiety has become important for many sports psychologists because of its important role in the achievement and the result that can be obtained, and therefore it is a double-edged sword either the negative impact is (anxiety disabled) or the positive impact is The importance of the research is that it is an attempt to identify and reduce this attribute as much as possible in the belief of researchers to develop the skill level of young volleyball players. The research aims to: 1. Identify the dimensions of the sports anxiety scale (facilitated anxiety and disability anxiety) among young volleyball players. 2. Identify the type of relationship between the dimensions of the sports anxiety scale (facilitated anxiety and disability anxiety) with the skills of transmission and reception of transmission among young volleyball players The sample of the research was represented by the young volleyball players of Baghdad clubs who participated in the sports season 2018-2019 and the number (108) players. The mathematical anxiety scale and its dimensions (facilitated anxiety and handicap anxiety) and experimental (transmission and reception of transmission) were used. 1. The presence of a significant difference between the dimension (facilitated anxiety) with the skills of transmission and receiving volleyball transmission for youth clubs in Baghdad province in the cases of high or low degree of dimension. 2. The presence of a significant difference between the dimension (facilitated anxiety) with the skills of transmission and receiving volleyball transmission for youth clubs Baghdad province. 3. The existence of a significant difference between the total score (for the measure of sports anxiety) with the skills of transmission and receiving volleyball transmission for youth clubs Baghdad province. The recommendations are: 1. The need to pay attention to the findings of the current study of the importance of knowing the degree of sports anxiety for each player and the amount of impact on the skill performance of volleyball. 2. The need to conduct similar studies to identify the type of relationship between sports anxiety with offensive and defensive skills in volleyball, which were not addressed in the current study. 3. The need to conduct similar studies are dealing with other psychological variables not addressed in the current study and try to know the type of relationship with the basic skills of volleyball and for both sexes.
Keywords: الصحة النفسية -- القلق الرياضي -- المهارات الرياضية -- اللاعبين الشباب -- الكرة الطائرة